The Fall of the Aztec Empire and its Dramatic Consequences - Testi, Dario (Mediterranean Journal of Social Sciences, 2011)
This article is an excerpt of a long and extensive work on Castilian and Portuguese geographical discoveries of the XV andXVI centuries. Among the jungles, deserts and snowy peaks of the, nowadays well known, central Mexico, takes place one of the mostinteresting, exciting and dramatic encounter in history. It is the 1519. On one side are the soldiers of Castile, armed with steel, on theother side of a huge cultural and mental barricade are the Aztecs, descendants of proud warriors who shed blood to conquer the Anahuacvalley and that, pouring out, more prepare to lose it. The article tries to summarize the main points of the military campaign known as"Conquest of Mexico" but also to investigate the actors, drawing upon the direct evidences of the protagonists of the event, the Aztec codesand the current interpretation of historians, anthropologists and archaeologists. The author's aim is to open up to the reader such adifferent world in the way of thinking, in the habits, in the warfare, torn by the irreconcilable dichotomy between sophistication andferocity, majestic temples and human sacrifices. Unfortunately this story has been misrepresented by historiographical clichÃ©s that hasidentified the good and the evil, the murderers and the martyrs. As an historian I have tried to maintain a proper intellectual and criticaldetachment and came to the inescapable conclusion that these are not bed men: these are men born and lived five centuries ago, withinsystems of thought and values opposed to those recognized today by the democratic nations.